EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KEMIRI (Aleurites moluccana WILLD.) PADA SISTEM LAHAN SALO SALUWAN DI KOTA PALU - Taiyeb, Asgar (Universitas Tadulako, 2017)
The background of this research are the establishing program of Candlenut (Aleurites moluccana Willd.) as MPTS by Agriculture, Forestry and Fishery Duty at the Salo Saluwan land System inÂ Palu City, Central Sulawesi. Salo Saluwan have slope > 40 % so that they are suitable to be developed and researched. Salo Saluwan has tree kinds of soil, it should be classified and evaluated of land suitability based on theirs kinds of soil. The aims of this research were: (a) evaluating the quality and characteristic of land of each kind of soil in that land system, and (b) classifying the suitability of existing land in that land system for the establishment of Candlenut plantation. Determination of land suitability for Candlenut using Atlas Format Procedures Method. The indicators used in determining the suitability of land for Candlenut is water and nutrient avalaible, the slope, the frequency of flooding, drainage, gravel and rock distribution and effective depth. Analysis result for land suitability of Candlenut in the Salo Saluwan show that most important finding: (a) type Latosol of soil developed at Salo Saluwan Land SystemÂ has marginally suitable (S3), while two kinds of them are not suitable (N) for the Candlenut plant growth, and (b) for the optimum growth of Candlenut, the limiting factor at three kinds of soils are low of water avalaible, and (c) for Latosol has other limiting factors, they are low of effective deepness and soil texture. In addition to Mediteran is low of effective deepness. Handling efforts of plant growth limiting factor such as fertilization, green manure, and mulch by efficient and effective after Candlenut plantation established at Salo Saluwan Land Sistem depend on soil and climate characteristic in Palu City.